The gyrfalcon (Falco rusticolus) genome - Zuccolo, A.; Mfarrej, S.; Celii, M.; Mussurova, S.; Rivera, L.F.; Llaca, V.; Mohammed, N.; Pain, A.; Alrefaei, A.F.; Wing, R.A. (Genetics Society of America, 2023)
High-quality genome assemblies are characterized by high-sequence contiguity, completeness, and a low error rate, thus providing the basis for a wide array of studies focusing on natural species ecology, conservation, evolution, and population genomics. To provide this valuable resource for conservation projects and comparative genomics studies on gyrfalcon (Falco rusticolus), we sequenced and assembled the genome of this species using third-generation sequencing strategies and optical maps. Here, we describe a highly contiguous and complete genome assembly comprising 20 scaffolds and 13 contigs with a total size of 1.193 Gbp, including 8, 064 complete Benchmarking Universal Single-Copy Orthologs (BUSCOs) of the total 8, 338 BUSCO groups present in the library aves_odb10. Of these BUSCO genes, 96.7% were complete, 96.1% were present as a single copy, and 0.6% were duplicated. Furthermore, 0.8% of BUSCO genes were fragmented and 2.5% (210) were missing. A de novo search for transposable elements (TEs) identified 5, 716 TEs that masked 7.61% of the F. rusticolus genome assembly when combined with publicly available TE collections. Long interspersed nuclear elements, in particular, the element Chicken-repeat 1 (CR1), were the most abundant TEs in the F. rusticolus genome. A de novo first-pass gene annotation was performed using 293, 349 PacBio Iso-Seq transcripts and 496, 195 transcripts derived from the assembly of 42, 429, 525 Illumina PE RNA-seq reads. In all, 19, 602 putative genes, of which 59.31% were functionally characterized and associated with Gene Ontology terms, were annotated. A comparison of the gyrfalcon genome assembly with the publicly available assemblies of the domestic chicken (Gallus gallus), zebra finch (Taeniopygia guttata), and hummingbird (Calypte anna) revealed several genome rearrangements. In particular, nine putative chromosome fusions were identified in the gyrfalcon genome assembly compared with those in the G. gallus genome assembly. This genome assembly, its annotation for TEs and ...